The effect of beer and its non-alcoholic ingredients on secretory and motoric function of the stomach - Franke, Andreas; Singer, Manfred V. (Beer in health and disease prevention, 2009)
Alcoholic beverages produced by fermentation like beer and wine strongly stimulate gastric acid secretion, whereas those produced by distillation (e.g. whisky, gin) have no stimulatory effect. Pure ethanol affects gastric acid secretion dose dependently: lower ethanol concentrations (1.4% and 4% v/v) have a mild, but significant stimulatory effect, whereas higher ethanol concentrations have no effect (5-10% v/v) or even a mild inhibitory effect (20% and 40% v/v). Non-alcoholic ingredients in alcoholic beverages produced by fermentation have to be responsible for the strong stimulation of gastric acid secretion. After separation by chromatography maleic acid and succinic acid could be identified to be responsible for the strong stimulatory effect of beer on gastric acid secretion. Alcoholic beverages and corresponding pure ethanol concentrations (4%, 10% and 40% v/v) are significantly slower emptied from the stomach than water: Gastric emptying of beer and wine, alcoholic beverages produced by fermentation, but not that of alcoholic beverages produced by distillation (e.g. whisky), is significantly slower than that of their corresponding ethanol solutions. Beer, other alcoholic beverages such as wine and whisky, and corresponding ethanol solutions (4% and 10% v/v) also inhibit gastric emptying of solid meals. The inhibitory effect results from a decelaration of the emptying phase, whereas in the initial lag-phase, the period of time between the end of consumption and the start of gastric emptying is unaffected by the alcoholic beverages.
Available online 29 January 2010
Gesehen am 24.03.2022